The effectiveness of the leadership transformation programme among off-campus students - Rohana Hamzah; Nurul Ain Fatehah Baharuddin; Wan Jumani Fauzi; Muhamad Afzamiman Aripin (Institute of Advanced Engineering and Science, 2019)
The social issues involving off-campus students are quite serious as these students are more susceptible to negative influences such as friends and the surrounding environment. Results from the preliminary study showed that there were four major problems which are relationship with the Creator, self-management, social relationship with housemates, as well as housekeeping management and upkeep. Therefore, an intervention programme named Transformation Leadership Programme for Off-Campus Students was designed. The study aimed to examine the effectiveness of the leadership transformation programme among off-campus student. The effectiveness of the intervention programme reported in this study is based only on pre- and post-tests from quantitative data collected from 30 respondents. The results show that there is no significant difference for the variable, ‘respondents’ belief in the Creator’ although the mean value increased in the post-test. Apart from that, the findings also show significant improvements in the other three variables assessed, (i.e., relationship with the Creator, self-management, social relationship with their housemates and housekeeping management and upkeep). Data also show that there was also positive impact on off-campus students’ academic achievement due to the decrease in the number of respondents with CGPA below 2.5. Therefore, this means the programme is successful in helping off-campus students to understand and make a connection between the value of belief in the Creator (spiritual intelligence) with the exercise of social responsibility as a leader to oneself, others and housekeeping management and upkeep.